Introduction to Basic Science in Early Childhood Through the Exploration Method of Surrounding Materials at TK Sosial Wagola - Waica Ladadia; Henny Henny; Hartati Hartati (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study employed a Classroom Action Research (CAR) design conducted with 14 children in Group B2 at TK Sosial Wagola. The intervention was implemented in two cycles, each consisting of four learning sessions. The success of the study was indicated by an improvement in children’s ability to recognize basic science concepts through the application of an exploration method using materials available in the surrounding environment, as well as increased children’s participation in learning activities. The results showed a significant improvement in children’s basic science recognition abilities, increasing from an average of 13% in the pre-action stage to 74% in Cycle I and reaching 93% in Cycle II. Introducing basic science from an early age is crucial as it fosters curiosity and develops children’s critical and logical thinking skills.